Jawa Pos Membela Persebaya : Bingkai Pemberitaan Jawa Pos tentang Persebaya dalam Kongres PSSI 2016 - Fajar Junaedi (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2016)
AbstractPersebaya, one of the great teams in the history of Indonesia, experienced a prolonged conflict with the PSSI. Before the PSSI Congress on 10 November 2016, PSSI promised to re-legalized Persebaya membership status in the PSSI, but in fact the promise of PSSI was unfulfilled. Jawa Pos, the largest newspaper of Surabaya -where Persebaya is originated from- allocated the first page and its sport page to proclaim the tackle of Persebaya membership status. In 10 to 12 November 2016 edition, Jawa Pos made the cancellation of Persebaya status as a headline. This study will be assessing for Jawa Pos’ news frame about the issue Persebaya membership in the PSSI on three-day publication mentioned above. By using William A. Gamson’s framing model analysis; the study finds that first, Jawa Pos frames on the PSSI’s promise to recognize Persebaya status in the PSSI Congress. In the second framing, Jawa Pos frames the news that PSSI had broken a promise, even Persebaya is the veracious side. Lastly, Jawa Pos frames the news that Persebaya still exist with proof Persebaya can perform the friendly match and supported by fourteen voter in the PSSI Congress. Thus, Persebaya should have the right to appear back in the official competition and be recognized once again as members of the PSSI.